2020
DOI: 10.3390/antiox9080755
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Product Accumulation in Subjects with Open-Angle Glaucoma with and without Exfoliation

Abstract: Advanced glycation end products (AGEs), which are the products of a non-enzymatic reaction between reducing sugars and other macromolecules, are critical in aging, as well as metabolic and degenerative diseases. To assess the involvement of AGEs in glaucoma, skin autofluorescence (sAF) level, which is a measurement of AGEs’ accumulation, was compared among Japanese patients with glaucoma (316 with primary open-angle glaucoma (PG) and 127 exfoliation syndrome and glaucoma (EG)) and controls (133 nonglaucomatous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
(92 reference statements)
2
12
0
1
Order By: Relevance
“…Significant differences in AGEs were observed by glaucoma type, with higher AGEs in EG and lower AGEs in PG ( Table 8 ). The result of AGEs in EG was consistent with our previous report [ 40 ]. Exfoliation products are produced by the aggregation of microfibrils [ 50 ], and the effect of AGEs via RAGE may enhance the production.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Significant differences in AGEs were observed by glaucoma type, with higher AGEs in EG and lower AGEs in PG ( Table 8 ). The result of AGEs in EG was consistent with our previous report [ 40 ]. Exfoliation products are produced by the aggregation of microfibrils [ 50 ], and the effect of AGEs via RAGE may enhance the production.…”
Section: Discussionsupporting
confidence: 93%
“…Upregulation of RAGE might cause early cell death of the RCGs [ 39 ]. AGEs levels were also measured percutaneously by the previously reported procedure using fingertip-measured skin autofluorescence (sAF) [ 40 ]. Among the AGEs, Nε-(carboxymethyl)-lysine (CML) was considered to be strongly involved in the pathogenic role, but it was difficult to detect directly because of the nonfluorescent feature of CML.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vascular dysfunction and neurodegeneration at the retina might be mediated by advanced glycation end products (AGEs), which are an oxidative stress-related biomarker that results from the reaction between reducing sugar with amino groups in proteins, lipids, or nucleic acids and is detected in the axons of RGCs and retinal glial cells in glaucoma. AGEs might activate signaling molecules as mitogen-activated protein kinases (MAPK) and nuclear factor kappa B (NF-kB), which induces ROS production, and the subsequent angiogenesis and neural apoptosis, which are related to immune responses as further described below [ 71 ]. In this way, Hondur et al reported that AGEs were higher in aqueous humor and blood samples in glaucomatous patients than in non-glaucomatous healthy patients [ 60 ].…”
Section: Oxidative Stress In Glaucomamentioning
confidence: 99%
“…Hondur et al [ 60 ] reported significantly higher levels of AGEs in blood and aqueous humor (AH) samples in glaucomatous patients compared to control. AGEs accumulation can also be detected using a sensor that determines the skin autofluorescence levels, which is correlated with AGEs [ 71 ].…”
Section: Diagnosismentioning
confidence: 99%